2021
DOI: 10.3389/fpsyg.2021.747187
|View full text |Cite
|
Sign up to set email alerts
|

Older and Younger Adults Perform Similarly in an Iterated Trust Game

Abstract: In social contexts, aging is typically associated with a greater reliance on heuristics, such as categorical information and stereotypes. The present research examines younger and older adults’ use of individuating and age-based categorical information when gauging whether or not to trust unfamiliar targets. In an adaptation of the iterated Trust Game, participants had to predict the cooperative tendencies of their partners to earn economic rewards in first encounters – in a context in which they knew nothing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
(87 reference statements)
1
7
1
Order By: Relevance
“…Across the three experiments, the overshadowing effect appeared in all eight conditions: when the partner was cooperative and non-cooperative, in a same-and mixed-gender pair, with ambiguous and non-ambiguous instructions. Although gender did not seem to interact with the overshadowing effect, we did observe a reliance on gender stereotypes at baseline with more cooperation with female than with male partners (Buchan et al, 2008;Telga & Lupiáñez, 2021), suggesting that this paradigm is sensitive to genderrelated biases. Thus, the results of the present study suggest that models of associative learning (e.g., Rescorla & Wagner, 1972), developed in the nonsocial domain and predominantly in research with nonhuman animals, may advance our understanding of human social cognition (Behrens et al, 2008;Heyes, 2012), including the processes underlying cooperation and trust (FeldmanHall & Dunsmoor, 2018).…”
Section: Discussioncontrasting
confidence: 59%
“…Across the three experiments, the overshadowing effect appeared in all eight conditions: when the partner was cooperative and non-cooperative, in a same-and mixed-gender pair, with ambiguous and non-ambiguous instructions. Although gender did not seem to interact with the overshadowing effect, we did observe a reliance on gender stereotypes at baseline with more cooperation with female than with male partners (Buchan et al, 2008;Telga & Lupiáñez, 2021), suggesting that this paradigm is sensitive to genderrelated biases. Thus, the results of the present study suggest that models of associative learning (e.g., Rescorla & Wagner, 1972), developed in the nonsocial domain and predominantly in research with nonhuman animals, may advance our understanding of human social cognition (Behrens et al, 2008;Heyes, 2012), including the processes underlying cooperation and trust (FeldmanHall & Dunsmoor, 2018).…”
Section: Discussioncontrasting
confidence: 59%
“…The S-IGT can be adapted in the future to incorporate additional facial stimuli attributes (e.g., race, age, sex, and emotion) to systematically examine their influences on trust learning across different populations. More exploration is needed on the effects of own-age, -sex, and -race biases as well as stereotype reliance on trust learning [62,63,84]. Further, the processing of positive and negative facial emotions can dynamically alter trustworthiness evaluations in others and adds complexity to social decision-making contexts as well as increased cognitive load, which should be considered in future experiments [17,26,85].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies did not find an interaction between trustee and trustor age. For instance, Telga and Lupianez (2021) used the trust game and found that there was no impact of partner or participant age. They analyzed the cooperation rates (i.e., whether to invest) instead of the exact investment, which might have caused the difference in results.…”
Section: Discussionmentioning
confidence: 99%
“…Although much research has focused on the effect of trustor and trustee age in face-based trust judgments, some research has not found an impact of trustor age on behavioral trust measures ( Sutter and Kocher, 2007 ; Rieger and Mata, 2013 ; Telga and Lupianez, 2021 ). Using the electroencephalogram (EEG) technique, researchers can further explore the cognitive mechanisms and temporal dynamics of trustworthiness perceptions in different age groups to determine whether individuals extract and process facial age cues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation